The research and verification of In-Arm Torsional Electromagnetic Active Suspension. (April 2021) - Han, Chengleng; Xu, Lin; Zou, Junyi; Abdelkareem, Mohamed AA; Cui, Enkang
This paper designs and manufactures a new type of arm suspension institution named In-Arm Torsional Electromagnetic Active Suspension (ITEAS) according to the structure and characteristic. The paper introduces the function and application scenarios of ITEAS and narrates the research value and scientific significance of the system. At first, the structure and principle of ITEAS are presented briefly, based on which the mathematical model of ITEAS suspension and height adjustment is built and analyzed. Next, the paper studies three critical components of ITEAS respectively. The mathematical solution is found to calculate the stiffness of the torsion bar. The structure and hydrodynamic model of the vane damper is researched, and the simulation model of the absorber is built in AMESim. The paper studies the theoretical principle of height adjustment and obtains the frequency characteristic of "Motor-Load" through the transfer function solved in MATLAB. Therefore, simulation models are built in AMESim in allusion to the three functions in the next chapter to verify the suspension characteristic, the height adjustment and the active displacement control of ITEAS independently. At last, several experiments are conducted on the test bench to check the feasibility of ITEAS. The results show that ITEAS is capable of being used as a vehicle suspension system and has a good impact on mitigation ability under road surface excitation, which enables us to adjust the body height and control the displacement actively according to the road condition.